2007
DOI: 10.1093/ejo/cjm065
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study of functional and morphological malocclusion trait changes from 3 to 12 years of age

Abstract: The aim of this study was to evaluate morphological and functional malocclusion trait changes in 3- to 12-year-old children and to determine whether such functional traits at the 3, 4, and 5 years of age correlated with malocclusion severity score at 12 years of age. Two hundred and sixty-seven children (132 boys, 135 girls) were randomly selected for a follow-up study from a previous cohort of 560 subjects. Functional and morphological traits were clinically assessed. Five functional malocclusion traits: mout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 23 publications
2
60
0
10
Order By: Relevance
“…Appealing study topics include the expansion of the classifications of deglutition (Peng et al, 2004;Ovsenik et al;Bertolini et al); the causes of atypical deglutition and its consequences (Cheng et al, 2002); diagnostic methods (Cayley et al; Bibby) age at its onset, and treatment methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Appealing study topics include the expansion of the classifications of deglutition (Peng et al, 2004;Ovsenik et al;Bertolini et al); the causes of atypical deglutition and its consequences (Cheng et al, 2002); diagnostic methods (Cayley et al; Bibby) age at its onset, and treatment methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is then considered as a dysfunction or abnormality because of its association with certain dental malocclusions and facial growing alterations (Peng et al, 2003;Graber et al, 1985). Such deglutition is classified as atypical (Peng et al, 2004;Ovsenik et al, 2007;Bertolini et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Todas estas variables y sus diferentes clasificaciones se tomaron según revisión de la literatura existente en el tema [17].…”
Section: Materiales Y Métodosunclassified
“…[3][4][5] Recent studies have investigated the swallowing pattern in relation to child development and have concluded that atypical swallowing is present in half of the children examined at the age of three years, but changes significantly after the age of six years.…”
Section: Introductionmentioning
confidence: 99%